Comparison between imprint cytology and frozen sections in intraoperative consultation of ovarian tumours - Ivan, Reily Ann; Chacko, Kuruvilla P.; Thomas, Pramod (International Journal of Research in Medical Sciences, 2020)
Background: The ovaries frequently are the site for various primary tumors. Correct intraoperative diagnosis is crucial. The application of imprint cytology is very useful where frozen section facility is not available. The present study is a comparison of imprint cytology and frozen section during intraoperative consultation for various types of benign and malignant ovarian neoplasms in different age groups. Methods: Seventy-six cases of ovarian tumors were examined using both imprint cytology and frozen section and evaluated, taking histopathological report as gold standard. The histopathological diagnoses consisted of benign (54), borderline (9), and malignant (13). The malignant tumors consisted of various types including serous carcinoma, mucinous carcinoma, endometrioid carcinoma, clear cell carcinoma and carcinoid. Results: All 54 benign cases were accurately diagnosed as benign by imprint cytology. With frozen section 53 cases were correctly diagnosed as benign but one case was over diagnosed as borderline. Among 13 malignant cases 11 (84.6%) were correctly diagnosed with both techniques. Borderline tumors were not able to be diagnosed with imprint smear, 3 out of 9 cases were correctly diagnosed with frozen section. Conclusion: When compared with frozen section, imprint cytology is a simple, inexpensive and useful diagnostic tool in intraoperative diagnosis of benign and malignant ovarian tumors. Imprint smear is not useful in borderline tumors where only frozen section is useful. Imprint cytology can be used as an adjunct to frozen section for better diagnosis.